God's waiting room : racial reckoning at life's end - Golomski, Casey (Rutgers University Press, 2025)
"Can older racists change their tune, or will they haunt us further once they're gone? Rich in mystery and life's lessons, God's Waiting Room: Racial Reckoning at Life's End considers what matters in the end for older white adults and the younger Black nurses who care for them. An innovation in creative nonfiction, Casey Golomski's years of immersive research at a nursing home in South Africa, thirty years after the end apartheid, are narrated as a one-day, room-by-room tour. Told in breathtakingly intimate and witty conversations with the home's residents and nurses, including the untold story of Nelson Mandela's Robben Island prison nurse, readers learn how ageism, sexism, and racism intersect and impact health care both in South Africa and in the United States, as well as create conditions in which people primed to be enemies find grace despite the odds. For copyright reasons, this edition is not available in the South African Development Community and Kenya"-- Provided by publisher.
Keywords: Nurse and patient -- South Africa.; Racism -- Health aspects -- South Africa.; Racism -- South Africa.; Nurses, Black -- South Africa.; Older white people -- South Africa.; South Africa -- Race relations.; Relations infirmière-patient -- Afrique du Sud.; Racisme -- Afrique du Sud.; Infirmières noires -- Afrique du Sud.; Afrique du Sud -- Relations raciales.; SOCIAL SCIENCE / General